2000
DOI: 10.4049/jimmunol.164.3.1582
|View full text |Cite
|
Sign up to set email alerts
|

Retrovirally Mediated IFN-β Transduction of Macrophages Induces Resistance to HIV, Correlated with Up-Regulation of RANTES Production and Down-Regulation of C-C Chemokine Receptor-5 Expression

Abstract: Constitutive expression of IFN-β by HIV target cells may be an alternative or complementary therapeutic approach for the treatment of AIDS. We show that macrophages derived from CD34+ cells from umbilical cord blood can be efficiently transduced by a retroviral vector carrying the IFN-β coding sequence. This results in resistance to infection by a macrophage-tropic HIV type 1, as shown by the drastic reduction in the HIV DNA copy number per cell and in p24 release. Moreover, IFN-β transduction totally blocked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 47 publications
(35 reference statements)
1
35
1
Order By: Relevance
“…However, none of the cytokine treatments affected the cell surface expression of CXCR4 or CCR5. This result contrasts with other studies that describe down-regulation of CXCR4 and CCR5 by IFN-␣ in PBMCs or cell lines and macrophages derived from CD34 ϩ cells from umbilical cord blood, respectively (69,70). Conversely, IL-7 up-regulated CXCR4 expression in T cells, PBMCs, and thymocytes, and this effect was associated with increased susceptibility to infection with X4 HIV strains (28,30,32,37).…”
Section: Discussioncontrasting
confidence: 55%
“…However, none of the cytokine treatments affected the cell surface expression of CXCR4 or CCR5. This result contrasts with other studies that describe down-regulation of CXCR4 and CCR5 by IFN-␣ in PBMCs or cell lines and macrophages derived from CD34 ϩ cells from umbilical cord blood, respectively (69,70). Conversely, IL-7 up-regulated CXCR4 expression in T cells, PBMCs, and thymocytes, and this effect was associated with increased susceptibility to infection with X4 HIV strains (28,30,32,37).…”
Section: Discussioncontrasting
confidence: 55%
“…Previous studies focusing on the effects of IFN-␤ have generated conflicting results. High doses of IFN-␤ (1 g/ml) were shown to reduce T cell production of the chemokinetic cytokines RANTES and MIP-1␣ and to reduce lymphocyte chemokinesis (15), but Cremer et al (16,17) found that IFN-␤ induced the production of RANTES in a variety of cell lines. However, the expression of the chemokine receptor CCR5 was down-regulated by IFN-␤, and the net effects of IFN-␤ on T cell migration were not examined.…”
mentioning
confidence: 99%
“…Herpes simplex and adenoviral vectors provide efficient cell transduction of macrophages in vitro, but their use for this purpose in vivo is limited by their immunogenicity. 46 Numerous studies have used retroviral vectors derived from Moloney murine leukemia virus 47 or lentiviruses 48 to transduce CD34+ cells ex vivo. Delivery of anti-HIV ribozyme, dominant negative proteins, or decoys to CD34+ cells partially protected progeny MDMs from HIV replication.…”
Section: Discussionmentioning
confidence: 99%
“…Delivery of anti-HIV ribozyme, dominant negative proteins, or decoys to CD34+ cells partially protected progeny MDMs from HIV replication. 47,[49][50][51][52] Recently, lentivirus vectors used to deliver RNAi against CCR5 were reported to transduce PBMC with low efficiency, and partially protect them from HIV replication. 53 We have found that rSV40 delivery of RNAi may be highly effective in protecting MDMs from R5-tropic HIV.…”
Section: Discussionmentioning
confidence: 99%